Students’ Prior Knowledge as an Ontogenic Obstacle on the Topic of Ratio and Proportion - Ayunda Sri Wahyuningrum; Didi Suryadi; Turmudi Turmudi (Jurnal Pendidikan Matematika, 2023)
This study aims to investigate students’ prior knowledge as an obstacle when learning ratio and proportion concept. The study uses an interpretive paradigm which is part of Didactical Design Research. Eighth graders who had learned about ratio and proportion participated in this study. The analysis was carried out qualitatively based on the data from the students’ answers and interviews on their answers when solving ratio and proportion problems to identify learning obstacle, especially ontogenic obstacle regarding the students’ prior knowledge. The result of this study indicates that prior knowledge is one of the ontogenic obstacle in teaching and learning of ratio and proportion. It can be found from their learning experience in understanding the concept. In conclusion, investigating students' prior knowledge is essential for the effectiveness of teaching and learning of ratio and proportion. It is important to overcome ontogenic obstacles and to understand how to activate students’ prior knowledge using the right or appropriate methods when learning ratio and proportion.